2015
DOI: 10.1155/2015/568634
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Protective Effects of Red Wine Extract, Resveratrol, in Oxidative Stress-Mediated Reperfusion Injury

Abstract: Resveratrol, a polyphenol extracted from red wine, possesses potential antioxidative and anti-inflammatory effects, including the reduction of free radicals and proinflammatory mediators overproduction, the alteration of the expression of adhesion molecules, and the inhibition of neutrophil function. A growing body of evidence indicates that resveratrol plays an important role in reducing organ damage following ischemia- and hemorrhage-induced reperfusion injury. Such protective phenomenon is reported to be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 172 publications
(223 reference statements)
0
38
0
Order By: Relevance
“…The pathophysiological mechanisms of IRI are primarily related to proinflammatory reactions, which include inflammatory responses, oxidative stress, and metabolic disorders [1, 3]. Resveratrol (RSV) is a stilbene polyphenolic compound found in grapes, berries, red wines, and peanut skins, and has been studied in many models such as coronary heart disease and diabetes due to its functions in reducing oxidative stress and inflammation [4-6]. In addition, many studies have shown that RSV can have protective effects on organs including the brain [7], heart [8], and kidney in animal IRI models because it reduces oxidative stress and exerts anti-inflammatory and anti-apoptotic effects [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanisms of IRI are primarily related to proinflammatory reactions, which include inflammatory responses, oxidative stress, and metabolic disorders [1, 3]. Resveratrol (RSV) is a stilbene polyphenolic compound found in grapes, berries, red wines, and peanut skins, and has been studied in many models such as coronary heart disease and diabetes due to its functions in reducing oxidative stress and inflammation [4-6]. In addition, many studies have shown that RSV can have protective effects on organs including the brain [7], heart [8], and kidney in animal IRI models because it reduces oxidative stress and exerts anti-inflammatory and anti-apoptotic effects [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Its sites of action include the cytomembrane, intra-cellular receptor, signaling molecules, enzymes, the oxidative system, the DNA repair system, transcription factors, cell proliferation, the cell cycle, differentiation and cell death (10,11). Cellular signaling pathways convert stimuli to signals.…”
Section: Introductionmentioning
confidence: 99%
“…The infiltration (Liu et al 2015). The epithelial-mucosal barrier is fortified by various cell adhesion molecules such as E-cadherin and a mucus layer containing different types of mucin, proteins altered by I/R injury as shown by Turner (Turner 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has also been suggested to prevent and treat ischemia and reperfusion injury due to its antioxidative activities (Liu et al 2015). Curcumin (1,7-bis(4-hydroxy-3-methoxy-phenyl)-1,6-heptadiene-3, 5 dione) is a yellow-orange dye extracted from the Indian spice turmeric.…”
Section: R a F T 4mentioning
confidence: 99%